2020
DOI: 10.1007/s00449-020-02322-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear on morphology, viability and metabolic activity of succinic acid-producing Actinobacillus succinogenes biofilms

Abstract: Two custom designed bioreactors were used to evaluate the effect of shear on biofilms of a succinic acid producer, Actinobacillus succinogenes. The first bioreactor allowed for in-situ removal of small biofilm samples used for microscopic imaging. The second bioreactor allowed for complete removal of all biofilm and was used to analyse biofilm composition and productivity. The smooth, low porosity biofilms obtained under high shear conditions had an average cell viability of 79% compared to 57% at the lowest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The complex nature of the model required a method to combine the interactions of the various parameters in a mechanistically interpretable way. A data set of pseudo-steady state biofilm results was compiled by combining results for pseudo-steady state fermentation studies by Maharaj et al [9], Brink & Nicol [10,26], Mokwatlo et al [21] (Error! Reference source not found.…”
Section: Expanded Analysis Of the Model At Pseudo-steady State Condit...mentioning
confidence: 99%
See 3 more Smart Citations
“…The complex nature of the model required a method to combine the interactions of the various parameters in a mechanistically interpretable way. A data set of pseudo-steady state biofilm results was compiled by combining results for pseudo-steady state fermentation studies by Maharaj et al [9], Brink & Nicol [10,26], Mokwatlo et al [21] (Error! Reference source not found.…”
Section: Expanded Analysis Of the Model At Pseudo-steady State Condit...mentioning
confidence: 99%
“…Within a biofilm system, the biofilm properties are a strong function of the history of the biofilm. Mokwatlo et al [20,21] showed that metabolite accumulation, specifically CSA, and external shear are major factors in the development of A. succinogenes biofilms. The data for Maharaj et al [9] were obtained in a packed bed system under very low shear conditions (0.04 m.s −1 ) and dilution rates between 0.054 and 0.72 h −1 , corresponding to SA titres between 32.5 g.L −1 and 11 g.L −1 .…”
Section: Expanded Analysis Of the Model At Pseudo-steady State Condit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Still, this depends on the process's flow regime, which reduces the liquid layer of nearby air bubbles and increases the k L a. However, using solid particles in the fermenter can lead to the hydrodynamic shearing of the biomass, impacting the morphology and viability of bacterial biomass [22] and even filamentous fungi more susceptible to shearing [23]. In this sense, the use of particles can be administered by limiting the aeration and agitation conditions of the medium.…”
Section: Introductionmentioning
confidence: 99%